Demographic and Occupational Differences Between Ethnic Minority Workers Who Did and Did Not Complete the Telephone Survey in English - Boyle, T.; Carey, Renee; Peters, S.; Glass, D.; Fritschi, L.; Reid, Alison (Oxford University Press, 2014)
Background/Objectives: Limited research indicates that using English language only surveys in prevalence studies conducted in the general population or in specific ethnic populations may result in unrepresentative samples and biased results. In this study, we investigated whether participants from ethnic minorities who chose to answer a study interview in a language other than English (LOTE) differed from those who completed the interview in English. Methods: This study was conducted within an Australian population-based telephone survey that assessed the prevalence of occupational exposure to carcinogens among 749 ethnic minority workers. We used modified Poisson regression to determine the factors associated with completing the interview in a LOTE. Results: Participants who elected to complete the interview in a LOTE differed from those who completed it in English on several factors, including sex, country of birth, education, occupation, and occupational exposure to carcinogens (40% compared with 29%, P < 0.01). Conclusions: The participants who chose to complete the study interview in their native language had several demographic differences from those participants who completed it in English, and were more likely to be exposed to carcinogens at work. Prevalence studies that offer only English language study instruments are unlikely to produce representative samples of minority groups, and may therefore produce biased results.